HER2 positivity as a predictor of brain metastases in breast cancer: A systematic literature review - Sakinah Mar'ie Sanad; I Made Oka Adnyana; I Putu Eka Widyadharma (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Breast cancer remains one of the most prevalent and lethal malignancies among women globally, which leads to the critical importance of early detection and a more comprehensive approach to breast cancer management. Purpose: To investigate HER2 positivity as a predictor of brain metastases in breast cancer. Methods: A total of 23 peer-reviewed studies published between 2015 and 2025 were analyzed, including randomized trials, retrospective cohorts, prediction model studies, and registry-based evaluations. Eligibility was guided by the PICOTS framework, and databases searched included PubMed, Scopus, MDPI, Elsevier, SagePub, and BMC Cancer. Results: The review confirms that HER2 overexpression significantly correlates with earlier brain metastasis onset, increased incidence, and distinctive treatment response profiles. HER2 status also influences survival outcomes and benefits from targeted agents such as trastuzumab, tucatinib, and pyrotinib. HER2-low expression additionally showed intermediate risk profiles, while imaging and circulating tumor cell data added prognostic value. Conclusion: HER2 positivity is a robust, independent predictor of brain metastasis in breast cancer patients. Routine integration of HER2 profiling in CNS risk assessment models may improve early detection and therapeutic precision, ultimately enhancing clinical outcomes for high-risk populations.